Return-on-investment of public investments to systems which provide public services - a case study - Simona Pichova; Jan Stejskal (European Regional Science Association (ERSA), 2015)
In recent years there have been frequent efforts to analyse the systems for providing public production and propose to increase the productivity and find alternative service-delivery mechanisms based on public-choice assumptions and perspectives. It is used an approach New public services, which is oriented and accountable to the citizens, aimed at ensuring maximum well-being of a new approach to public production. It highlights the changing role of the public sector - from service delivery role into the policy development. It is necessary to solve a major problem. Public administrators have long struggled with how to measure outcomes of public programs because the performance measurement tools have traditionally neglected. The article presents the information about return-on-investment analysis and it build on the results of the project focused on the ROI analysis in municipal libraries in the Czech Republic. The data was obtained from the biggest public library of Czech Republic ? from Municipal Library of Prague (MLP). The survey was conducted in year 2012 as a qualitative and representative through an online questionnaire where was addressed 11,397 randomly selected readers of MLP. The return on the survey was 20 %, after the data file cleaning the basic set consists a 2227 of respondents. The calculation of the ROI value is performed by using the calculation of cost/benefit analysis. Input data - costs for providing of evaluated portfolio of the public services - into the cost/benefit analysis were obtained from MLP. These financial resources in the form of cost of the MLP are public investments because they come from the public budgets of the regional level. The result of the study presented in this paper is a calculating ROI for public investment. The methodology for ROI calculating of the public services systems is a very valuable tool for regional providers of public services and their investments. Through their assistance, regional providers can better orientate themselves when spending money and can make better decisions as to which services they will provide and to what extent. For the analysed library, it was found that its operation and provision of a selected range of library services is generally effective, but the rate of effectiveness is relatively low, approaching a value of one. Analysed library has a range of services what was defined which in turn are not effective. The methodology also monitors the extent to which individual services are used and economically evaluated by the consumers themselves. This data can be used both for the management of each library and their owners and regional donors. This was the first research of this type in this branch of the public sector with a high degree of representativeness, which has been implemented in Central and Eastern Europe.
Keywords: H72; H41; D61; 330; public investments; public services; return-on-investment analysis; library